Social Responsibility of Higher Education Students. Motivations for its Development in Times of Covid-19 in Chile and El Salvador - SEVERINO-GONZÁLEZ, Pedro; ROMERO-ARGUETA, José; VILLALOBOS ANTÚNEZ, José Vicente; GARRIDO-VÉLIZ, Viviana (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT The Covid-19 health crisis has led to reflection on various aspects of human life from the perspective of their behavior in society. The purpose of this research is to analyze the social responsibility of university students in Chile and El Salvador, to make way for an EFA and an analysis of media differences. This allows identifying the motivations for its development and implementation. The highest valuation is concentrated in Chileans and, in most cases; differences are presented according to the categories in this investigation. Future research should consider several areas of behavior for higher education students. RESUMEN La crisis de salud producto de Covid-19 ha llevado a la reflexión sobre diversos aspectos de la vida humana desde la perspectiva de su comportamiento en la sociedad. El propósito de esta investigación es analizar la responsabilidad social de los estudiantes universitarios en Chile y El Salvador, para dar paso a una AFE y un análisis de las diferencias de medias. Lo que permite identificar las motivaciones para su desarrollo e implementación. La valoración más alta se concentra en los chilenos y, en la mayoría de los casos se presentan diferencias significativas según las categorías presentadas en esta investigación. Las futuras investigaciones deben considerar varias áreas de comportamiento para los estudiantes de educación superior.